Distributed fiber optic vibration sensor based on polarization fading model for gas pipeline leakage testing experiment. Issue 3 (September 2018) - Wang, Qiang; Han, Linjuan; Fan, Xinwei; Zhu, Jianyun
To design a distributed fiber optic vibration sensor for urban natural gas pipeline leak detection, the light polarization fading transmission model based on Jones matrix is built in this mixed Sagnac/Mach-Zehnder interferometer configuration. The interference light intensity of pipeline with leakage and without leakage cases is compared through spectrum analyzer. When fiber length ranges from 1.5 to 9.5 km, the light power intensity (central wavelength 1550 nm) reduces to −56 dB. In experiment, the leaky spectrum null frequencies are captured and the average relative error of leakage point location varies from 2.3 to 5.3%. When the sensing length is expanded to 9.5 km, the vibration sensor system sensitivity is 0.57 Hz/m.